Physiological and Pathophysiological Roles of Metabolic Pathways for NET Formation and Other Neutrophil Functions - Stojkov, Darko; Gigon, Lea; Peng, Shuang; Lukowski, Robert; Ruth, Peter; Karaulov, Alexander; Rizvanov, Albert; Barlev, Nickolai A.; Yousefi, Shida; Simon, Hans-Uwe (Frontiers in Immunology, 2022)
Neutrophils are the most numerous cells in the leukocyte population and essential for innate immunity. To limit their effector functions, neutrophils are able to modulate glycolysis and other cellular metabolic pathways. These metabolic pathways are essential not only for energy usage, but also for specialized effector actions, such as the production of reactive oxygen species (ROS), chemotaxis, phagocytosis, degranulation, and the formation of neutrophil extracellular traps (NETs). It has been demonstrated that activated viable neutrophils can produce NETs, which consists of a DNA scaffold able to bind granule proteins and microorganisms. The formation of NETs requires the availability of increased amounts of adenosine triphosphate (ATP) as it is an active cellular and therefore energy-dependent process. In this article, we discuss the glycolytic and other metabolic routes in association with neutrophil functions focusing on their role for building up NETs in the extracellular space. A better understanding of the requirements of metabolic pathways for neutrophil functions may lead to the discovery of molecular targets suitable to develop novel anti-infectious and/or anti-inflammatory drugs.